2021
DOI: 10.1016/j.tree.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Photogrammetry as a tool to improve ecosystem restoration

Abstract: Ecosystem restoration has been practiced for over a century and is increasingly supported by the emergent applied science of restoration ecology. A prerequisite for successful ecosystem restoration is determining meaningful and measurable goals. This requires tools to monitor success in a standardized way. Photogrammetry uses images to reconstruct landscapes and organisms in three dimensions, enabling non-invasive measurement of key success indicators with unprecedented accuracy. We propose photogrammetry can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 59 publications
0
26
0
2
Order By: Relevance
“…With the rise in remote sensing technologies (Section ‘ On the rise of remote‐sensing technologies in ecology ’), the idea of translating some metric of habitat complexity (e.g. obtained from scanning diverse or pristine natural environments) into real‐world solutions is tantalising (Calders et al, 2020 ; Ferrari et al, 2021 ). These solutions range from replanting or introducing trees and habitat‐forming species to adding physical elements to manipulate habitat structure in both natural and urban environments (Morris et al, 2019 ; Palmer et al, 2010 ).…”
Section: Applied Significancementioning
confidence: 99%
See 1 more Smart Citation
“…With the rise in remote sensing technologies (Section ‘ On the rise of remote‐sensing technologies in ecology ’), the idea of translating some metric of habitat complexity (e.g. obtained from scanning diverse or pristine natural environments) into real‐world solutions is tantalising (Calders et al, 2020 ; Ferrari et al, 2021 ). These solutions range from replanting or introducing trees and habitat‐forming species to adding physical elements to manipulate habitat structure in both natural and urban environments (Morris et al, 2019 ; Palmer et al, 2010 ).…”
Section: Applied Significancementioning
confidence: 99%
“…Complexity metrics are also being used as success indicators for restoration programs. It has been suggested that techniques such as photogrammetry will improve restoration success by enabling the measurement of complexity with ‘unprecedented accuracy’ (Ferrari et al, 2021 ). Again, this premise is built on the assumption that we already have reliable, accurate metrics of complexity; but, unfortunately, we do not.…”
Section: Applied Significancementioning
confidence: 99%
“…0.25 m 2 quadrats (Ohara et al 2021), with a restricted range of metrics collected. However, the development of underwater imaging tools such as 'structure from motion' (SfM) photogrammetry now enables researchers to track millimetre-scale changes in reef environments over large areas (> ~ 500 m 2 ) within a single dive (Bayley and Mogg 2020;Ferrari et al 2021). Survey locations can then be repeatedly returned to once marked, using photogrammetry to track various changes at the frequency of choice-be it days or years (Magel et al 2019;Bongaerts et al 2020;Cresswell et al 2020).…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Traditionally, 3D growth forms in corals have been measured, including destructive computed tomography (CT; Foster et al, 2016) or non‐destructive ‘structure from motion’ (SfM; Friedman et al, 2012; Young et al, 2017). This latter work has included 3D reconstruction of individual colonies that are precise to the mm range (Ferrari et al, 2021; Lange & Perry, 2020; Million et al, 2021) or 3D scanning of the benthos over large areas (e.g. the ReefCloud program), including field photogrammetry of reefscapes.…”
Section: Introductionmentioning
confidence: 99%